High magnetic and ferroelectric properties of BZT-LSM multiferroic composites at room temperature - Pakpoom Jarupoom (2018)
© 2018 Elsevier Ltd and Techna Group S.r.l. In this research, the effects of La0.7Sr0.3MnO3additive on the phase evolution, microstructure, dielectric, ferroelectric and magnetic properties of BaZr0.07Ti0.93O3ceramics were systematically investigated. The (BaZr0.07Ti0.93O3)/x(La0.7Sr0.3MnO3) or BZT/xLSM (where x = 0, 5, 10 and 20 mol%) ceramics were prepared via a solid state reaction method. A pure perovskite phase is observed for the samples of x ≤ 10 mol%. The M-H hysteresis loops also show an improvement in the magnetic behavior for higher LSM content samples as well as the modified ferroelectric properties. However, the 5 mol% sample exhibited the optimum ferroelectric and ferromagnetic properties with remnant magnetization (Mr) and remanent polarization (Pr) of 2.38 emu/g and 10.5 µC/cm2, respectively. The dielectric-temperature curves show that the two phase-transition temperatures as observed for the unmodified BZT ceramic merges into a single phase-transition temperature for the 5 mol% sample and then become flat curves for the 10 mol% sample. In addition, the mechanical properties i.e. Knoop hardness and Young's modulus values increase with increasing LSM content, where Knoop hardness and Young's modulus values for the 20 mol% sample are increased by ~ 45% and ~ 104%, respectively, as compared to the unmodified sample.